John Hay papers - Hay, John, 1838-1905.
Correspondence and letterbooks, speeches, diaries, notebooks, scrapbooks, memorabilia, memoranda, and other papers relating chiefly to Hay's service as U.S. ambassador to Great Britain and U.S. secretary of state under William McKinley and Theodore Roosevelt. Earlier papers deal with his work as a lawyer in Springfield, Ill., his poetry, and his years with the New York Tribune, as well as his years, 1861-1864, as assistant secretary to Abraham Lincoln. Includes material concerning the Spanish-American War. Also includes correspondence dated 1882-1914 of his wife, Clara Louise Stone Hay (1849-1914), an autograph collection pertaining primarily to slavery in the U.S., and a land grant, 1798, issued by Kentucky to the grandfather of Abraham Lincoln and his heirs.
Correspondents include Brooks Adams, Alvey A. Adee, Joseph Hodges Choate, George B. Cortelyou, Charles William Eliot, Henry James, Clarence King, Henry Cabot Lodge, William McKinley, Baron Julian Pauncefote, William Woodville Rockhill, Theodore Roosevelt, Elihu Root, Sir Cecil Spring Rice, and Mark Twain.
Microfilm edition of containers 1-39 available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Rare Book and Special Collections Division.
Statesman, diplomat, historian, journalist, and poet.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Brooks, -- 1848-1927 -- Correspondence; Adee, Alvey A. -- 1842-1924 -- Correspondence; Choate, Joseph Hodges, -- 1832-1917 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Eliot, Charles William, -- 1834-1926 -- Correspondence; Hay, Clara Louise Stone, -- 1849-1914 -- Correspondence; James, Henry, -- 1843-1916 -- Correspondence; King, Clarence, -- 1842-1901 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; McKinley, William, -- 1843-1901.; McKinley, William, -- 1843-1901 -- Correspondence; Pauncefote, Julian, -- Baron, -- 1828-1902 -- Correspondence; Rockhill, William Woodville, -- 1854-1914 -- Correspondence; Roosevelt, Theodore, -- 1858-1919.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Spring Rice, Cecil, -- Sir, -- 1859-1918 -- Correspondence; Twain, Mark, -- 1835-1910 -- Correspondence; New York tribune; American newspapers -- New York; American poetry; Diplomatic and consular service, American -- Great Britain; Land grants -- Kentucky; Law -- Illinois; Slavery -- United States; Spanish-American War, 1898.; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- 1897-1901.; United States -- Foreign relations -- 1901-1909.; United States -- Foreign relations -- Great Britain; United States -- History -- Civil War, 1861-1865.; Authors; Cabinet officers; Diplomats; Journalists; Poets; Statesmen